Neovascular glaucoma as a complication of proton therapy for uveal melanoma - I.E. Panova; E.M. Svistunova; N.A. Vorobyov; E.V. Samkovich; N.I. Martynova; A.A. Bykhovsky (РМЖ "Клиническая офтальмология")
I.E. Panova1,2,3, E.M. Svistunova1, N.A. Vorobyov2,4, E.V. Samkovich1, N.I. Martynova4, A.A. Bykhovsky1 1Saint Petersburg Branch of the S. Fyodorov Eye Microsurgery Federal State Institution,   St. Petersburg, Russian Federation 2St. Petersburg State University, St. Petersburg, Russian Federation 3North West State Medical University named after I.I. Mechnikov, St. Petersburg,   Russian Federation 4Medical and Diagnostic Center of the International Institute of Biological Systems   named after Berezin Sergei, St. Petersburg, Russian Federation Aim: to evaluate possible predictors of neovascular glaucoma (NVG) in patients with uveal melanoma (UM) after pencil-beam scanning proton therapy (PT). Patients and Methods: 29 UM patients (30 eyes; age: 23–87 years) received a course of hypofractionated PT at a total dose of 49 Gy in 7 fractions (BED 0.6=620 Gy; EQD2=143 Gy). After the therapy, radiation-related complications developed in 26 patients at various times, and in some cases they affected multiple systems. Ocular hypertension was reported in 13 patients, and NVG developed in 9 of them. NVG predictors were evaluated in groups of NVG patients (Study Group/SG 1) and non-NVG ones (SG 2) with a ≥6-month follow-up (n=22) after the end of the PT course. Results: the NVG group demonstrated lower best corrected visual acuity (BCVA) and total visual field loss (along 8 meridians, in degrees) values, as well as pre-treatment Bruch's membrane rupture and more advanced stage of the disease significantly (p<0.05) more often than the non-NVG group. Conclusion: the study revealed some possible predictors of neovascular glaucoma development that should be considered to select patients for pencil-beam scanning PT in terms of organ preservation UM treatment. Further study of the issue in a larger patient cohort and a longer follow-up will provide identification of additional risk factors for NVG and generation of a mathematical prediction model of the complication development. Keywords: choroidal melanoma, proton therapy, uveal melanoma, ocular oncology, neovascular glaucoma, radiation-related complications. For citation: Panova I.E., Svistunova E.M., Vorobyov N.A., Samkovich E.V., Martynova N.I., Bykhovsky A.A. Neovascular glaucoma as a complication of proton therapy for uveal melanoma. Russian Journal of Clinical Ophthalmology. 2024;24(4):185–192 (in Russ.). DOI: 10.32364/2311-7729-2024-24-4-4